2022
DOI: 10.1155/2022/3740856
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Velocity Modulation and Clinical Efficacy of Acupuncture for Posterior Circulation Infarction Vertigo: A Systematic Review and Meta-Analysis

Abstract: Background. Vertigo is a cardinal symptom of posterior circulation infarction (POCI). Acupuncture is demonstrated to have a beneficial effect on posterior circulation infarction vertigo (PCIV). However, the mechanism of acupuncture therapy is not clarified. This study aims to assess the cerebral blood flow velocity modulation and clinical efficacy of acupuncture for PCIV patients. Methods. We conducted this systematic review for clinical randomized controlled trials (RCTs) regarding acupuncture on PCIV. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Different SA points or areas from various parts of the scalp may produce different effects on rCBF, as such, the duration or intensity of acupuncture may also affect these effects. In a meta-analysis study, the effect of acupuncture was measured on the posterior circulation infarction vertigo (PCIV) that included 20 RCTs (1,541 participants) ( Li et al, 2022 ). This study showed that acupuncture improved the vertebrobasilar blood flow velocity and achieved good efficacy for patients with PCIV.…”
Section: Effects Of Scalp Acupuncture On Cerebral Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Different SA points or areas from various parts of the scalp may produce different effects on rCBF, as such, the duration or intensity of acupuncture may also affect these effects. In a meta-analysis study, the effect of acupuncture was measured on the posterior circulation infarction vertigo (PCIV) that included 20 RCTs (1,541 participants) ( Li et al, 2022 ). This study showed that acupuncture improved the vertebrobasilar blood flow velocity and achieved good efficacy for patients with PCIV.…”
Section: Effects Of Scalp Acupuncture On Cerebral Blood Flowmentioning
confidence: 99%
“…Although it has been reported that needling the scalp could improve CBF even without repeatedly manipulation of the needles, for example, when the needles were inserted at Fengchi (GB20) and Dazhui (GV14) clockwise to a depth of 15–20 mm, twirled at a angle, and retained for 30 min, an improvement in CBF in ICA and MCA could be observed ( Yang et al, 2021 ), traditionally, SA usually emphasizes the need for repeated rapid rotation or lifting-thrusting of needles during treatment ( Wang, 2019 ). It was reported that when SA was used to treat patients with PCIV, a longer treatment course (sessions) and stronger stimulation (intensity) are more effective in improving vertebrobasilar blood flow velocity and clinical efficacy ( Li et al, 2022 ).…”
Section: The Relative Specificity Of Scalp Acupuncture In Regulating ...mentioning
confidence: 99%
“…[1] In many previous clinical studies and trials, Chinese medicine has effectively treated vertigo. [9][10][11][12] Based on this evidence, we hypothesized that acupuncture might effectively treat HSC-BPPV. Here, we report the case of a 70-year-old patient diagnosed with HSC-BPPV.…”
Section: Introductionmentioning
confidence: 99%